The Direct Strength Method for first generation trapezoidal steel sheeting under Interior One Flange and Interior Two Flange web crippling. (November 2022) - Hofmeyer, H.; Geers, S.W.A.; Snijder, H.H.; Schafer, B.W.
Abstract: Trapezoidal steel sheeting is a popular product in the built environment, especially for roofing and cladding. However, at a support the webs of the sheeting may fail due to concentrated force, referred to as web crippling. In this paper it is investigated whether the Direct Strength Method (DSM) can be used to predict this failure. First, an experimental programme, carried out in the past, is selected for its sheet section dimensions, materials, span lengths, and load bearing plate widths which were varied systematically. Two distinct failure mechanisms occurred: the yield arc and the rolling mechanisms. Based on the experiments, in this paper a finite element model is developed to simulate Interior One Flange (IOF) and Interior Two Flange (ITF) web crippling, and a very good correlation is obtained with the experiments. Subsequently, the simulations are used to predict the buckling load (via the first positive Eigenvalue), the yield load (via first plastic strains or stress extrapolation), and the ultimate load for each experiment and additional cases. In addition, for each failure mechanism, an existing theoretical model is used to predict the first order elasto-plastic mechanism initiation load. Six different DSM equations are calibrated for both IOF and ITF web crippling, using the above different buckling and yield loads. For IOF cases, the use of the IOF first positive Eigenvalue for the buckling load, and the first order elasto-plastic mechanism initiation load, results in the best correlation and coefficient of variation. For ITF cases, the ITF Eigenvalue and same yield load shows the best results. Excluding the rolling mechanism, the DSM correlates equally (IOF) or better (ITF) with the numerical results than the AISI S100-16 design rule. Thus, the DSM, as a generalized slenderness approach, is suited for IOF and ITF web crippling of first generation trapezoidal steel sheeting. Furthermore, it could be considered to allow for the use of the well performing FE models explicitly by the codes—e.g. enabling manufacturers to create tables of strength. Highlights: IOF and ITF web crippling experiments simulated. FE simulations provide Eigenvalues, yield load, ultimate load. Theoretical model provides mechanism initiation load. DSM equations are derived for different load types. DSM correlates equally (IOF) or better (ITF) than AISI S100-16.